The Vocabulary-Comprehension Relationship across the Disciplines: Implications for Instruction - Janis Harmon; Karen Wood (MDPI AG, 2018)
The main purpose of vocabulary instruction is to enhance and support reading comprehension. This goal spans across the grade levels and different disciplines and is supported by a plethora of research. In recent years, a great deal of needed attention has been finally given to academic vocabulary and disciplinary literacy. To contribute to this body of knowledge, we believe it is critical to examine how the complex relationship between vocabulary and comprehension may be addressed in secondary content area classrooms, given the unique nature of the academic vocabulary students encounter daily in school. This conceptual paper contains the following: (1) definition of academic vocabulary; (2) description of what is known about the vocabulary–comprehension relationship; (3) conceptualization of the intersection of academic vocabulary and the vocabulary–comprehension relationship; and (4) instructional implications emerging from this intersection. Perhaps this conceptualization may provide disciplinary practitioners more insight to help them make decisions regarding vocabulary instruction.